Usefulness of saliva for perampanel therapeutic drug monitoring - Kim, Do‐Yong; Moon, Jangsup; Shin, Yong‐Won; Lee, Soon‐Tae; Jung, Keun‐Hwa; Park, Kyung‐Il; Jung, Ki‐Young; Kim, Manho; Lee, SeungHwan; Yu, Kyung‐Sang; Jang, In‐Jin; Song, KaHeon; et al. (Epilepsia (Copenhagen), 2020)
Objective Therapeutic drug monitoring (TDM) of antiepileptic drugs (AEDs) helps optimize drug management for patients with epilepsy. Salivary testing is both noninvasive and easy, and has several other advantages. Due to technical advances, salivary TDM has become feasible for several drugs, including AEDs, and its value has been investigated. Until recently, saliva TDM of perampanel (PER) had not been reported. The purpose of our study was to confirm whether saliva is a biological substitute for plasma in PER TDM. Methods Adult patients diagnosed with epilepsy who received PER from August 2018 to March 2019 at Seoul National University Hospital were enrolled. Total and free PER were measured in simultaneously obtained plasma and saliva samples using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) and high‐performance liquid chromatographic (HPLC). We examined the correlations between saliva and plasma PER concentrations and whether the use of concomitant medications classified as cytochrome P450 (CYP)3A4 inducers affected the correlations. Results Thirty patients were enrolled, aged 16 to 60; 10 (33%) were women. Patients received 2 to 12 mg (mean, 6 mg) of PER. The average total and free concentrations of PER were 343.02 (46.6‐818.0) and 1.53 (0.51‐2.92) ng/mL in plasma and 9.74 (2.21‐33.0) and 2.83 (1.01‐6.8) ng/mL in saliva, respectively. A linear relationship was observed between the total PER concentrations in saliva and the total and free PER concentrations in plasma (both P < .001; r = .678 and r = .619, respectively). The change in the PER concentration caused by the CYP3A4 inducer did not affect the correlation between saliva and plasma concentrations (all P < .001). Significance The PER concentration in saliva was correlated with that in plasma. This correlation was not affected by CYP3A4 inducers. Our results demonstrate for the first time that PER is measurable in saliva and suggest the potential for the clinical application of the saliva PER TDM matrix.